Factors effect on the effective length in a double strap joint between steel plates and CFRP - Majid Mohammed Ali Kadhim (Institute of Advanced Engineering and Science, 2012)
This paper presents the behavior of axially loaded flat steel plates strengthened using carbon fiber reinforced polymer sheets. Two steel plates were joined together with adhesive and followed by the application of carbon fiber sheet double strap joint with different bond lengths. The effective length of CFRP sheet has been study by using commercially available finite element analysis software ANSYS V12.1. A parametric study has been performed by numerical modeling with the variables of CFRP sheet thickness, adhesive layer thickness, steel plate thickness and number of CFRP sheet layer.